THEORETICAL ASPECTS OF THE INTERACTION OF RELIGION AND LAW - Водоласкова, Катерина Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the scientific article is to study of the fundamental problem of human society in relation to religious and legal norms in their conceptual and historical aspects. The relevance of the study of this topic is due to the tension between law and religion, which, although it has existed since ancient times, but in recent years has gained global scope and intensity. Research methods: formal-dogmatic and historical, method of interpretation (interpretation), synergetic approach, analysis and synthesis, as well as comparative legal method. Results: identify an approach to a synergistic understanding of religion and law for further harmonization of elements of society as a system in modern conditions. Discussion: finding ways to improve interdependence and coherence between religious and legal norms. As a rule, people attribute religion and law to different spheres of life. However, this positioning does not objectively reflect the synergetic relationship between these systems, as law and religion are two full-fledged aspects and two dimensions of social experience, but they are interrelated. Despite the tensions between them, one cannot prosper without the other. Thus, law without religion is reborn into mechanical legalism. Religion without right loses its social effectiveness. Most of the institutional and structural components of religion and law are similar or identical: purpose, methods of influence, structure, object of relations, etc. The author of the article aims to devote to the study of dialectical synthesis, the synthesis of opposites. Unfortunately, modern social trends and world events force us to focus on the distinction between law and religion and not enough on their fundamental unity. Therefore, it is necessary to consider the balance of elements and synergistic interaction of these two systems in the broadest sense. In this article, law is understood as a system and process of division of rights and responsibilities in society, and religion - as the intuition of society and the commitment to the ultimate meaning and purpose of life. When the understanding of these systems narrows, the institutional ties between these two dimensions are also severed and there is a risk of demoralizing society, ie existing institutional structures and processes lose their sanctity and, conversely, the sacred values on which society is based are seen as simple hypocrisy.